2017
DOI: 10.1007/s12011-017-0986-2
|View full text |Cite
|
Sign up to set email alerts
|

The Concentration of Vanadium in Pathologically Altered Human Kidneys

Abstract: Vanadium has a unique and beneficial effect on both humans and animal organisms; however, excessive amount of the above-mentioned metal can cause many alterations in tissues and organs, including the kidneys. The aim of the study was to determine the concentration of vanadium (V) in the kidneys removed from patients due to lesions of various etiologies, including the rejection of the transplanted kidneys. Additionally, we determined the influence of selected biological and environmental factors on the V concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…Data has been presented on the concentrations of copper in human kidneys; however, many publications do not specify whether these values relate to the cortical or medullar parts of the kidney. It is believed that the concentration of heavy metals depends on the part of the organ [35, 36]. Additionally, various biological and environmental factors affect the accumulation of trace elements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data has been presented on the concentrations of copper in human kidneys; however, many publications do not specify whether these values relate to the cortical or medullar parts of the kidney. It is believed that the concentration of heavy metals depends on the part of the organ [35, 36]. Additionally, various biological and environmental factors affect the accumulation of trace elements.…”
Section: Introductionmentioning
confidence: 99%
“…It has been also reported that there is an association between the etiology of the disease and the concentrations of trace elements within kidneys [13, 24, 35, 36]. Our earlier studies have indicated that renal grafts accumulate less cadmium, lead, mercury, and vanadium than the kidneys, with other pathological alterations [35, 36]. No data has been found regarding the comparison of concentration of Cu between rejected renal grafts and cancerous kidneys.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study indicated that cadmium, lead, and mercury concentrations are statistically lower in renal grafts than in cancerous kidneys [32]. Moreover, we documented decreased levels of vanadium and copper in renal grafts [33,35]. This may have been caused by the immunosuppressive drugs used by the transplant recipients.…”
Section: Introductionmentioning
confidence: 56%
“…There was also a significant upregulation of ATPase gene activity in the LL and DD groups. ATPase is generated in the mitochondria and participates in oxidative phosphorylation in order to produce ATP [65, 66]. It is well known that ATP decomposition releases energy to promote cell growth, cell division and other vital movements [67].…”
Section: Discussionmentioning
confidence: 99%